ANTAGONISTIC ACTIVITY OF MACROMYCETES AGAINST MUCOR SP IFBG 139 - Т. А. Круподьорова; В. Ю. Барштейн (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2019)
Aim. To screen macromycetes for their ability to show antagonistic activity against Mucor sp. IFBG 139 micromycete. Methods. Antagonistic activity of the representatives of 30 macromycetes against Mucor sp. IFBG 139 has been determined by the method of dual cultures. Results. The studied macromycetes showed low antagonistic activity against to the selected strain of Mucor sp. IFBG 139. The domination of unilateral antagonism of Mucor sp. IFBG 139 has been established: overgrowth of micromycete without deadlock was noted on 4 species, partial and complete overgrowth after deadlock at the mycelial contact was found on 11 species, on 9 species, respectively. Bilateral antagonism has been revealed for certain species, inhibition of macromycetes varied from 38.9 to 51.1%, and for micromycete from 54.4 to 77.7%. Mutual deadlock at the contact was observed for 5 basidiomycetes species: Crinipellis schevczenkoi, Fomitopsis pinicola (the same level of inhibition has been established), Ganoderma applanatum, Laetiporus sulphurеus, Lyophyllum shimeji) and ascomycete Ophiocordyceps sinensis. Results. The obtained data supplement information about antagonism of the studied fungi species. Maximal inhibition index of Mucor sp. IFBG 139 growth has been found with F. pinicola co-cultivation. Lentinula edodes inhibit the growth of micromycete, producing antifungal metabolites against Mucor sp. IFBG 139. These two xylotrophic basidiomycete species can be a biotechnological objects for further research in oder to study their antifungal substances and to create a potentially effective fungicidical products.